Information of the Sixth Conference of the Lithuanian Mathematical Society - Journal, Lithuanian Mathematical (Lithuanian Mathematical Journal, 1965)
Original title in Russian and Lithuanian:Информация о Шестом республиканском совещании Литовского математического обществаInformacija apie šeštąjį respublikinį Lietuvos matematikų pasitarimą